Estetika Sebagai Motivasi Pelisanan dalam Mabebasan di Bali - Bawa, Anak Agung Gede; Sukartha, I Nyoman (Humanis; Vol 25 No 2 (2021), 2021)
Research on aesthetics as a motivation for memorizing the oral of mabebasan in Bali uses a qualitative approach. Data collection uses the methods of reading and listening to parwa, kakawin, kidung, and geguritan when mabebasan activity takes place. Mabebasan is a traditional sound art that functions to accompany ceremonies and also as entertainment. The method of analysis was carried out with a qualitative conceptual using descriptive-analytic techniques based on the working stages of the semiotic theory which correlates with the theory of needs motivation. The result of the analysis is presented using informal method with systematic and structured explanations as well as the formal method. The result of the research provide the answer that aesthetics in the form of sound game, word game, meaning game, language style (stylistics/ alamkara), and art sound are the motivators for oral (mabebasan). The existence of stylistics / alamkara is sung with melodious and chanting rhythms as well as the value causing the memorization of the oral in mabebasan.